Characteristics of Choir Recording, In the Creation of Composer Mustafo Bafoyev - qizi, Abdulazizova Oydinoy Muxamadin (Research Parks Publishing LLC, 2023)
The article is dedicated to the analysis of the works of Mustafa Bafoyev, who wrote the subtle aspects of the choir, in various genres, and attention is paid to revealing its musical potential.